2014
DOI: 10.1042/bj20140793
|View full text |Cite
|
Sign up to set email alerts
|

Modification by covalent reaction or oxidation of cysteine residues in the tandem-SH2 domains of ZAP-70 and Syk can block phosphopeptide binding

Abstract: Zeta-chain Associated Protein of 70kDa (ZAP-70) and Spleen tyrosine kinase (Syk) are non-receptor tyrosine kinases that are essential for T-cell and B-cell antigen receptor signaling, respectively. They are recruited, via their tandem-SH2 domains, to doubly-phosphorylated Immunoreceptor Tyrosine-based Activation Motifs (ITAMs) on invariant chains of immune antigen receptors. Because of their critical roles in immune signaling, ZAP-70 and Syk are targets for the development of drugs for autoimmune diseases. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
(44 reference statements)
0
26
0
1
Order By: Relevance
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…Another study has shown that treatment with peroxide impaired CD3-mediated phosphorylation of Zap-70 (Chakravarti and Abraham, 2002). A more recent study has identified C39, which is located in the phosphotyrosine-binding pocket of the N-terminal SH2 domain of Zap-70, as a possible target of oxidation (Visperas et al, 2015). The proposed model postulates that H 2 O 2 oxidizes this cysteine, thus preventing the recruitment of the Zap-70 SH2 domain to the phosphorylated ITAMs and ultimately attenuating TCR signaling (Figure 2).…”
Section: What Are the Targets Of Ros?mentioning
confidence: 96%
“…We have previously reported FP assays for measuring the ZAP-70:ITAM interaction. 8,10 Here, we describe the development and optimization of this assay for use in a high-throughput screen.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis showed these hit compounds to be cysteine-dependent covalent modifiers of ZAP-70, as described. 8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation